Sepsis management in pre-hospital care – the earlier, the better? - Lazzarin, Taline [UNESP]; Ballarin, Raquel Simões [UNESP]; Zornoff, Leonardo [UNESP]; Tanni, Suzana Erico [UNESP]; Paiva, Sergio Alberto Rupp de [UNESP]; Azevedo, Paula Schmidt [UNESP]; Minicucci, Marcos Ferreira [UNESP] (Springer Nature, 2024)
Emergency medical services often serve as the initial point of contact for septic patients, offering crucial pre-hospital intervention opportunities. However, the efficacy of pre-hospital interventions remains uncertain. From this perspective, we’ll talk about the available evidence of pre-hospital sepsis and septic shock treatment and the barriers to its implementation.
Keywords: Antibiotics; Pre-hospital emergency care; Sepsis; Septic shock